From Glory to Decline: Reasons Behind the Decline of Muslims - Narendra Jumadil Haikal Ramadhan; Yusuf Hanafi (Journal of Islamic History, 2024)
This paper is a review of the book "Limadza Taakhkharal Muslimun wa Limadza Taqaddama Ghairuhum" by Al-Amir Syakib Arslan. This book succinctly presents the reasons for the decline of Islam, providing an initial introduction for those studying the history of the decline of Islam. The study of this subject is all the more interesting because despite the passage of more than half a century, Muslims have still not achieved their former glory. This study needs to be reexamined in light of the current context. The importance of this study is further reinforced by the fact that understanding the causes of the past decline can provide valuable insights for designing strategies for the future revival of Muslims.